Contribution of prostanoid signaling to the evolution of spreading depolarization and the associated cerebral blood flow response - Varga Dániel Péter; Puskás Tamás; Menyhárt Ákos; Hertelendy Péter; Zölei-Szénási Dániel; Tóth Réka; Ivánkovits-Kiss Orsolya; Bari Ferenc; Farkas Eszter (2016)
The significance of prostanoid signaling in neurovascular coupling during somatosensory stimulation is increasingly more appreciated, yet its involvement in mediating the cerebral blood flow (CBF) response to spreading depolarization (SD) has remained inconclusive. Selective cyclooxygenase (COX) enzyme inhibitors (NS-398, SC-560) or an antagonist (L161,982) of the EP4 type prostaglandin E2 receptor were applied topically to a cranial window over the parietal cortex of isoflurane-anesthetized Sprague-Dawley rats (n = 60). Global forebrain ischemia was induced by occlusion of both common carotid arteries in half of the animals. SDs were triggered by the topical application of 1M KCl. SD occurrence was confirmed by the acquisition of DC potential, and CBF variations were recorded by laser-Doppler flowmetry. EP4 receptor antagonism significantly decreased peak hyperemia and augmented post-SD oligemia in the intact but not in the ischemic cortex. COX-1 inhibition and EP4 receptor blockade markedly delayed repolarization after SD in the ischemic but not in the intact brain. COX-2 inhibition achieved no significant effect on any of the end points taken. The data suggest, that activation of EP4 receptors initiates vasodilation in response to SD in the intact brain, and - together with COX-1 derived prostanoids - shortens SD duration in the acute phase of ischemia.